Dante's Vision and the Circle of Knowledge - Mazzotta, Giuseppe, 1942- (Book collections on Project MUSE., 1993)
In a masterly synthesis of historical and literary analysis, Giuseppe Mazzotta shows how medieval knowledge systems--the cycle of the liberal arts, ethics, politics, and theology--interacted with poetry and elevated the Divine Comedy to a central position in shaping all other forms of discursive knowledge. To trace the circle of Dante's intellectual concerns, Mazzotta examines the structure and aims of medieval encyclopedias, especially in the twelfth and thirteenth centuries; the medieval classification of knowledge; the battle of the arts; the role of the imagination; the tension between knowledge and vision; and Dante's theological speculations in his constitution of what Mazzotta calls aesthetic, ludic theology. As a poet, Dante puts himself at the center of intellectual debates of his time and radically redefines their configuration. In this book, Mazzotta offers powerful new readings of a poet who stands amid his culture's crisis and fragmentation, one who responds to and counters them in his work. In a critical gesture that enacts Dante's own insight, Mazzotta's practice is also a fresh contribution to the theoretical literary debates of the present. Originally published in 1992. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.